Altered functional connectivity within default mode network after rupture of anterior communicating artery aneurysm - Chen, Fuxiang; Kang, Yaqing; Yu, Ting; Lin, Yuanxiang; Dai, Linsun; Yu, Lianghong; Wang, Dengliang; Sun, Xi; Kang, Dezhi (Frontiers in Aging Neuroscience, 2022)
Background: Rupture of anterior communicating artery (ACoA) aneurysm often leads to cognitive impairment, especially memory complains. The medial surperior frontal gyrus (SFGmed), a node of default mode network (DMN) has been extensively revealed to participate in various cognitive processes. However, the functional connectivity (FC) characteristics of SFGmed and its relationship with cognitive performance remain unknown after rupture of ACoA aneurysm. Methods: Resting-state functional magnetic resonance imaging and cognitive assessment were acquired in 27 eligible patients and 20 controls. Seed-based FC between unilateral SFGmed and the rest of brain were calculated separately, and then compared their intensity differences between two groups. Furthermore, we analyzed correlation between abnormal FC and cognitive function in patients with ruptured ACoA aneurysm. Results: Cognitive impairment was confirmed in 51.9% of the patients. Compared with the controls, patients suffering from ruptured ACoA aneurysm exhibited a similar FC decline between each side of SFGmed and predominant nodes within DMN, including the precuneus, angular gyrus, cingulate cortex, left hippocampus, left amygdala, left temporal pole, and left medial orbitofrontal cortex. Besides, significantly decreased FC of left SFGmed and left insula, right middle temporal gyrus as well as right medial orbitofrontal cortex were also found. In addition, only enhanced insular connectivity with right SFGmed was determined, whereas increased FC of the left SFGmed was not observed. Correlation analyses showed that lower total cognitive performance or stronger subjective memory complains were related to reduced connectivity in the SFGmed and several cortical regions such as angular gyrus and middle cingulate cortex. Conclusion: Our results suggest that patients with ruptured ACoA aneurysm exist long-term cognitive impairment and intrinsic hypoconnectivity of cognition-related brain regions within DMN. Deactivation of DMN may be a potential neural mechanism leading to cognitive deficits in these patients.